1997
DOI: 10.1007/s001250050733
|View full text |Cite
|
Sign up to set email alerts
|

Renal function and insulin resistance as determinants of plasma leptin levels in patients with NIDDM

Abstract: Leptin is a newly found hormone secreted by adipocytes [1]. It is the ob gene product which regulates food intake and thermogenesis [2][3][4]. The ob/ob mouse has a mutation in the ob gene [1], and db/db mice have a mutation in the gene coding for the leptin receptor [5,6]. Therefore, leptin could play an important role in the pathogenesis of obesity and diabetes mellitus. In humans, however, the majority of obese subjects have elevated plasma leptin concentrations [7][8][9], suggesting the presence of leptin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 24 publications
5
28
1
Order By: Relevance
“…For the second experiment, eight subjects (age 23.4 Ϯ 0.6 yr, height 171.1 Ϯ 2.6 cm, weight 61.0 Ϯ 2.6 kg) were tested for a measurement of glucose uptake by using a hyperinsulinemic-euglycemic clamp, according to the method by DeFronzo et al (6), with the aid of a blood glucose monitoring and glucose-insulin infusion system (Artificial Pancreas model STG22; Nikkiso, Tokyo, Japan) (22,45). After an overnight fast, subjects arrived at a clinical research room in Kyoto University Hospital at 8:30 AM and were kept in the supine position with both knees extended.…”
Section: Subjectsmentioning
confidence: 99%
“…For the second experiment, eight subjects (age 23.4 Ϯ 0.6 yr, height 171.1 Ϯ 2.6 cm, weight 61.0 Ϯ 2.6 kg) were tested for a measurement of glucose uptake by using a hyperinsulinemic-euglycemic clamp, according to the method by DeFronzo et al (6), with the aid of a blood glucose monitoring and glucose-insulin infusion system (Artificial Pancreas model STG22; Nikkiso, Tokyo, Japan) (22,45). After an overnight fast, subjects arrived at a clinical research room in Kyoto University Hospital at 8:30 AM and were kept in the supine position with both knees extended.…”
Section: Subjectsmentioning
confidence: 99%
“…Finally, it is interesting to note that leptin also activates JAK\STAT [39]. Given that leptin might be associated with obesity and insulin resistance in patients with non-insulin-dependent diabetes mellitus [40] and that leptin receptors are present in the kidney [39], it remains to be studied whether leptin could be induced by AGE.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In humans, circulating leptin concentrations are related to the degree of renal function, assessed by 1aplasma creatinine. 22 In contrast, it has been recently reported that intact leptin is increased in patients with end-stage renal disease, although increased production may account for the high concentrations of leptin. 23 Serum leptin concentrations are markedly elevated in the patients with chronic renal failure and higher plasma insulin, than in those with lower plasma insulin concentrations.…”
Section: Introductionmentioning
confidence: 86%
“…40 Leptin receptor mRNA was detected in the liver of rodents 22,23 and the addition of leptin, increases hepatic cell proliferation. 41 It is possible that an increase in circulating leptin concentrations may partially work as the proliferation factor of hepatocellular carcinoma cells in LC patients.…”
Section: Leptin In Liver Cirrhosis H Shimizu Et Almentioning
confidence: 99%